Domestic inquiry in the private sector / Libat Langub - Langub, Libat (Faculty of Law, 1982)
Industrial discipline is an important aspect of master-servant relationship, or in modern parlance, the employer-employee relationship. It is necessary for the efficient functioning of any organisations. The employers and employees have their own part to play to maintain a high level of discipline. What is meant by "industrial discipline"? There is no statutory definition for industrial discipline and normally it is understood to mean punishment but it is more than this. Punishment is the negative side of discipline. Industrial discipline can be viewed as training that seek to correct the erring employee. On the part of the employees, it is the observance of regulations and rules in an industrial establishment for the maintenance of control and order. The Management, on the other hand, has a right to take action against an erring employee. Industrial discipline is important to the Management, industry, individual employee and the nation as a whole. Many cases that go to the Industrial Court on discipline, usually involves dismissal, and most industrial disputes arise directly or indirectly from here. Perhaps the reason lies in the fact that when an employee is dismissed by the Management he loses his livelihood and losing a job is almost tantamount to capital punishment. Thus, it is pertinent to examine the scope of disciplinary actions and proceedings.